Effect of Remote Ischemic Preconditioning on Perioperative Cardiac Events in Patients Undergoing Elective Percutaneous Coronary Intervention: A Meta-Analysis of 16 Randomized Trials - Xiangming Wang; Na Kong; Chuanwei Zhou; Deeraj Mungun; Zakaria Iyan; Yan Guo; Zhijian Yang (Cardiology Research and Practice)
Background. The main objective of this meta-analysis was to investigate whether remote ischemic preconditioning (RIPC) reduces cardiac and renal events in patients undergoing elective cardiovascular interventions. Methods and Results. We systematically searched articles published from 2006 to 2016 in PubMed, EMBASE, Web of Science, Cochrane Library, and Google Scholar. Odds ratios (ORs) with 95% confidence intervals (CIs) were used as the effect index for dichotomous variables. The standardized mean differences (SMDs) with 95% CIs were calculated as the pooled continuous effect. Sixteen RCTs of 2435 patients undergoing elective PCI were selected. Compared with control group, RIPC could significantly reduce the incidence of perioperative myocardial infarction (OR = 0.64; 95% CI: 0.48–0.86; P=0.003) and acute kidney injury (OR = 0.56; 95% CI: 0.322–0.99; P=0.049). Metaregression analysis showed that the reduction of PMI by RIPC was enhanced for CAD patients with multivessel disease (coef.: −0.05 [-0.09;-0.01], P=0.022). There were no differences in the changes of cTnI (P=0.934) and CRP (P=0.075) in two groups. Conclusion. Our meta-analysis of RCTs demonstrated that RIPC can provide cardiac and renal protection for patients undergoing elective PCI, while no beneficial effect on reducing the levels of cTnI and CRP after PCI was reported.